Assessment of damage and residual load bearing capacity of a concrete slab after fire: Applied reliability-based methodology. (1st November 2017) - Molkens, Tom; Van Coile, Ruben; Gernay, Thomas
Highlights: Reliability-based assessment of the post-fire residual capacity of a concrete slab. Comprehensive methodology introduced through application to a real-life case study. Information obtained through inspections, tests, and modelling can be combined. Only existing simplified method for reliability-based post-fire assessment. The proposed methodology can be easily applied by practicing engineers. Abstract: For most fires occurring in buildings with a concrete structural frame, the structural elements do not collapse during fire exposure, and further use of the building after fire may be possible. Fire can nevertheless result in a permanent loss of strength and thus a post-fire evaluation of the residual load bearing capacity has to be made to inform decisions on continued use and the need for structural repairs. This evaluation is however particularly difficult due to the many uncertainties associated with both the fire exposure and the characteristics of the structural elements. These uncertainties cannot be neglected when determining the residual capacity since adequate safety is a major societal concern as indicated by the predominance of safety in current design standards and guidance documents. In this paper a comprehensive methodology is presented for the assessment of the residual capacity of concrete structures after exposure to fire. The methodology is introduced through application to a real-life case study of an apartment fire with a focus on the end-span of the affected continuous concrete slab. It results in a reliability-based evaluation of the maximum allowable characteristic value for the imposed load on the slab. The presented methodology is useful to make informed decision about continued use of structures after a fire event.